Intelligent Transportation System based on Blockchain for Mitigating Routing Attacks - Mada K. ALHARBI; Abdulatif ALABDULATIF; Tarek MOULAHI; Mohamed Ben OTHMAN (Communications of International Proceedings, 2021)
The rapid increase of vehicle traffic volume in modern societies raises the need to develop innovative solutions to reduce traffic congestion and enhance traffic management efficiency. The intelligent transportation system (ITS) is an advanced technology that enables improved traffic management. However, ITS suffers from routing issues in the network layer causing routing attacks that threaten the availability of ITS services (e.g., black-hole and gray-hole attacks). In this research, a Blockchain-based smart contracts model is proposed to offer a security mechanism to ITSs.
Keywords: ITS; VANET; black-hole; gray-hole.